Sosialisasi Pengelolaan Sampah Mandiri Melalui Kegiatan Pemberdayaan RT Menuju Lingkungan Bersih dan Produktif Di Kota Batam - Asmarawati, Citra Indah; Wibowo, Sadiq Ardo (Jurnal Tiyasadarma, 2024)
Independent waste management in Batam City through empowering neighbourhood is a strategic solution to overcome the challenge of increasing waste volume, with a comprehensive approach that includes outreach, technical implementation and multi-party collaboration. This program aims to transform society's paradigm towards waste, from mere waste to a valuable resource, while encouraging active participation by citizens in creating a clean and productive environment. To increase community awareness and capacity at the neighbourhood level in Batam City in managing waste independently, effectively and sustainably, so as to create a clean and productive environment through a community empowerment approach. This activity was in partnership with selected neighbourhood, involving a total of 20 participants consisting of neighbourhood administrators and resident representatives. Implementation methods include introductory seminars, practical workshops, environmental cadre training, and implementation of pilot projects in selected neighbourhood, with data collection through pre-post surveys, field observations, and in-depth interviews with key participants. Program evaluation is carried out through analysis of changes in waste volume, level of citizen participation, and the economic impact of independent waste management activities. Community service activities focus on socializing independent waste management through empowering neighbourhood in Batam City, involving situation analysis, material development, environmental cadre training, and implementation in selected neighbourhood. This program succeeded in increasing awareness and participation of citizens in waste management, with concrete results in the form of reducing the volume of waste going to TPS by 50% in six months, increasing citizens' understanding by 80%, and creating additional income from the sale of compost and recycled products. The socialization program for independent waste management based on neighbourhood empowerment in Batam City has shown significant success in increasing public awareness, reducing waste volume and creating economic value, so it has the potential to be replicated in other areas.